Syed Muhammad Naquib Al-Attas' Concept Of Justice In Addressing Gender Equality Issues - Al Faritzi, Muhamad Redho; Herlambang, Muhammad Giri (Civilization Research: Journal of Islamic Studies, 2025)
This research discusses the concept of justice according to Syed Muhammad Naquib Al-Attas as an alternative solution to the problem of contemporary gender equality. The aim is to describe the meaning of justice ('adl) according to Al-Attas and examine its relevance in responding to demands for absolute equality between men and women. The method used is a literature study with a qualitative approach and content analysis of Al-Attas' works related to the concept of justice and human nature. The results show that justice, in Al-Attas' view, is a harmonious condition when everything is in its place and function in accordance with the nature and purpose of creation. In the context of gender, justice does not mean uniformity of roles, but rather fair placement based on the rights, responsibilities, and natures of each. The novelty of this research lies in offering a paradigm of fitrah-based justice as a critique of the Western concept of gender equality. The implication is that this approach can prevent misunderstanding of gender differences while emphasising the importance of the Islamic worldview in building fair and harmonious gender relations.